2016
DOI: 10.1002/jrs.4929
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman spectroscopy investigation of the carbonation reaction in a lime paste produced with a traditional technology

Abstract: Micro‐Raman spectroscopy has been used to follow the carbonation reaction up to 16 weeks in lime paste produced with a traditional technology and cured under controlled conditions. The transformation of calcium hydroxide into calcium carbonate was visualised using Raman Imaging. Calcite was the only crystalline CaCO3 polymorph detected under the conditions of the experiment. Three sharp zones of pure portlandite (Ca(OH)2), partially carbonated portlandite and calcite (CaCO3), could be distinguished. Amorphous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…It has been reported that when CH has left in an open container prolonged time, the reaction of carbonatation has formed about 30% (wt%) of the medication after 1 month (Cohen & Lasfargues, 1988). It has been reported that the CH mass have almost fully carbonatation after 16 weeks (Ševčík et al, 2016). However, it has been reported that 90% of the CH remained unconverted into CaCO 3 after 6 weeks within the root canal in vivo (Kwon et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been reported that when CH has left in an open container prolonged time, the reaction of carbonatation has formed about 30% (wt%) of the medication after 1 month (Cohen & Lasfargues, 1988). It has been reported that the CH mass have almost fully carbonatation after 16 weeks (Ševčík et al, 2016). However, it has been reported that 90% of the CH remained unconverted into CaCO 3 after 6 weeks within the root canal in vivo (Kwon et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…These ions generate to introduce hard tissue formation on vital tissue and the antibacterial effect on bacteria (Estrela & Pesce, 1996). Moreover, Ca 2+ ions interact with atmospheric or tissue‐related carbon dioxide (CO 2 ) or carbonate ions (CO 3− ) in an aqueous medium (Ševčík et al, 2016). Therefore, Ca 2+ ions come into contact with vital tissue calcium carbonate salt is formed which is called carbonatation (Kwon, Fujishima, & Imai, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro‐Raman spectroscopy was used by Ševčík et al to follow the carbonation reaction, up to 16 weeks, in lime paste produced with a traditional technology and cured under controlled conditions. Moreover, authors visualized the transformation of calcium hydroxide into calcium carbonate using Raman Imaging.…”
Section: Conservation Issues (Alteration/degradation Processes) Affecmentioning
confidence: 99%
“…Raman microscopy has been used to study the hydration of C 3 S, 25 weathering of anhydrous cements, 26 and carbonation of lime paste. 27 However, its application for real-time imaging of cement-based materials remains under-explored. Torres-Carrasco et al 28 and Mikhailova et al 29 used Raman microscopy to study the hydration of Portland cement and polymerisation of alkali-activated cement and their results show that Raman microscopy is a promising tool for in situ observation of phase evolution in cement-based materials.…”
Section: Introductionmentioning
confidence: 99%